Syncytial Variant of Nodular Sclerosis Hodgkin Lymphoma: A Case Report on Histological Medley of Morphological Variants - CD Anand; Ruchismita Pal; R Anitha; Kothai Gnanamoorthy; Muthu Sudalaimuthu (Journal of Clinical and Diagnostic Research)
There are several histological and morphological subtypes of Hodgkin Lymphoma (HL), a malignant lymphoproliferative disease, and each has distinct prognostic consequences. Syncytial Variants is an unique, uncommon morphological type of Nodular Sclerosis Hodgkin Lymphoma (SV-NSHL). Unlike other subtypes of classical HL, which exhibit a male preponderance, it is more prevalent in females. The most often affected lymph nodes, which can exhibit contiguous spread, are the cervical or mediastinal lymph nodes, or both. Hereby, the authors present a case report of an 18-year-old male patient who has been experiencing intermittent fever, weight loss, neck pain, and gradual enlargement of the neck and axillary lymph nodes over the past two months presented to the Outpatient Department (OPD). Clinical examnation and radiological assessment using plain Computed Tomography (CT) of chest scan showed several enlarged lymph nodes in the mediastinum and anterior chest wall, along with sternum erosion. This led to a differential diagnosis of lymphoma, sarcoidosis, and atypical tuberculosis. Histological analysis {Haematoxylin and Eosin (H&E)} and immunohistochemical profiling of an excised left supraclavicular lymph node rendered the diagnosis of classic HL, and a very rare variant, the SV-NSHL. The present case is being reported for its extreme rarity, diagnostic challenges, and distinct clinicopathological correlation.